2010
DOI: 10.1515/jpm.2010.079
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for evaluating uterine cervical consistency using vaginal ultrasound gray-level histogram

Abstract: A more echogenic anterior than posterior cervix indicates a hard cervix; the greater the difference in echogenicity between anterior and posterior walls the harder the cervix. The difference in MGL of the ultrasound gray-level histogram may enable objective evaluation of cervical consistency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 9 publications
1
19
0
2
Order By: Relevance
“…15,8083 The lack of association between strain in the sagittal plane and spontaneous preterm delivery can be related to the mixture of strain values from different areas of the cervix. Applying other methods, such as ultrasound attenuation, 8486 gray-level histogram characteristics, 87,88 or shear wave elastography, 78,79,89 or using reference materials for strain comparisons, 90 may allow for the reliable evaluation of cervical regions other than the internal os.…”
Section: Discussionmentioning
confidence: 99%
“…15,8083 The lack of association between strain in the sagittal plane and spontaneous preterm delivery can be related to the mixture of strain values from different areas of the cervix. Applying other methods, such as ultrasound attenuation, 8486 gray-level histogram characteristics, 87,88 or shear wave elastography, 78,79,89 or using reference materials for strain comparisons, 90 may allow for the reliable evaluation of cervical regions other than the internal os.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the AP difference in the control group was not found to be as high as the AP difference in the SUI group. This finding shows that the normal posterior midurethra, unlike the anterior cervix in the study of Kuwata et al [24], might not be so consistent that it absorbs much of the ultrasound beam. Instead, the posterior midurethra absorbed the ultrasound beam less easily, and the anterior and posterior regions had approximately the same echogenicity in the continent women.…”
Section: Discussionmentioning
confidence: 82%
“…Chou et al [23] postulated that this information allows for a more detailed investigation of the endometrium, thus reducing invasive procedures. Finally, Kuwata et al [24] evaluated cervical consistency using vaginal ultrasound gray-level histograms. The authors evaluated the anterior and posterior cervix in pregnant women and related it to the Bishop subscores.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been used to estimate cervical consistency (Yamaguchi 2007;Molina 2012), elastography requires special equipment and categorizes stiffness only qualitatively. Some inventive methods using only B-mode ultrasonography have also been attempted (Ross 2007;Kuwata 2010;Parra-Saavedra 2011). ParraSaavedra's cervical consistency index (CCI) innovatively represents cervical consistency in a quantitative manner by measuring the diameter of the deformity caused by compression.…”
Section: Introductionmentioning
confidence: 99%